PROBATIVE VALUE OF HIGHER FORENSIC MEDICAL BOARD”S OPINIONS - Alina-Marilena ŢUCĂ (Challenges of the Knowledge Society)
There are situations in which the judicial bodies need the opinion of an expert in order to ascertain, clarify or assess facts or circumstances that are important for finding out the truth. Forensic expert examinations fall into a specific category relative to other types of examinations as they can be carried out only by forensic medical institutions subordinated to the Ministry of Health. The supreme scientific authority in the field of forensic medicine is the Higher Forensic Medical Board attached to the “Mina Minovici” Forensic Medicine Institute in Bucharest. The mission of this board is to verify, assess, analyse and endorse from a scientific point of view, upon the request of judicial bodies, the contents and conclusions of various forensic medical documents performed by other subordinate public institutions, authorised by law to carry out fact-finding and expert examinations. This article aims at clarifying the probative value in criminal proceedings of the opinions issued by this supreme authority, because there have been and are situations in judicial practice in which higher probative value has been rendered to such opinions, as well as situations in which its conclusions have been disregarded in a reasoned manner.